2021
DOI: 10.21037/tlcr-20-541
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio for advanced non-small cell lung cancer patients with high PD-L1 tumor expression receiving pembrolizumab

Abstract: Background: We investigated the association of peripheral blood inflammatory markers with overall survival (OS) in pembrolizumab treated advanced non-small cell lung cancer (aNSCLC) patients with programmed death ligand 1 (PD-L1) expression ≥50%. Clinical risk factors for development of immunerelated adverse events (irAE) were also explored.Methods: aNSCLC patients with high PD-L1 expression receiving pembrolizumab monotherapy outside of clinical trials were identified retrospectively. All patients were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…The results of our analysis for baseline NLR, PLR and MLR revealed the relationship between low values and better survival outcomes, confirming the aforementioned exposure. The current findings are in agreement with those reported in several previous studies (24,26,27,32,40) Similarly, the results for PLR showed that elevated values were related to poor survival (OS: HR =1.93, 95% CI: 1.51-2.01, P<0.001 and PFS: HR =1.57, 95% CI: 1.30-1.90, P<0.001). Furthermore, in a study of a large cohort (1,466 cases) of patients who underwent curative resection with stage I-IIIA NSCLC, Yuan et al (27) concluded that elevated MLR was an independent predictor for poor OS (HR =1.25, 95% CI: 1.01-1.54, P=0.035).…”
Section: Discussionsupporting
confidence: 93%
“…The results of our analysis for baseline NLR, PLR and MLR revealed the relationship between low values and better survival outcomes, confirming the aforementioned exposure. The current findings are in agreement with those reported in several previous studies (24,26,27,32,40) Similarly, the results for PLR showed that elevated values were related to poor survival (OS: HR =1.93, 95% CI: 1.51-2.01, P<0.001 and PFS: HR =1.57, 95% CI: 1.30-1.90, P<0.001). Furthermore, in a study of a large cohort (1,466 cases) of patients who underwent curative resection with stage I-IIIA NSCLC, Yuan et al (27) concluded that elevated MLR was an independent predictor for poor OS (HR =1.25, 95% CI: 1.01-1.54, P=0.035).…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have shown that NLR and PLR are associated with OS in lung cancer patients treated with ICIs ( 46 48 ). However, the relationship between these indicators and the OS of patients with CIP is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…A high neutrophil to lymphocyte ratio (NLR) in serum is known to correlate with worsened ICI clinical outcome (95)(96)(97). Although its predictive correlation with all irAEs is mostly weak, NLR distinguishes grade 3 and higher irAEs from low grade irAEs after pembrolizumab therapy and it can be used to monitor the onset of irAEs (98,99). For IMC in particular, a baseline NLR higher than 5 correlated with development of IMC (100).…”
Section: Cellular Indicatorsmentioning
confidence: 99%